STUDI KASUS ANALISIS BEBAN KERJA BERDASARKAN WAKTU KERJA KARYAWAN PADA UNIT PEMANENAN AFDELING 1 DI KEBUN KELAPA SAWIT PT. XYZ - Muhammad Irwansyah Barkhati Setiawan; Arief Rahman; Faradilla; Muhammad Atta Bary (JURNAL AGRIMENT, 2021)
The importance of quality human resources in oil palm plantations in the field of harvesting to achieve high productivity, the success of harvesters is also very much determined by the pressure of the workload that is owned by workers, the workload depends on the job description compiled by the company. also the possibility of a workload that is too high. This study aims to analyze the working time of harvest employees and determine the productive, unproductive and personal time of harvest employees and analyze the number of harvest employees needed at PT. XYZ. This research was conducted at PT. XYZ Tanjung Batu Village, Derawan Island District, Berau Regency, East Kalimantan. This research was conducted using work sampling data collection method, namely observing the working time of harvest employees with 10 minutes intervals for 7 working hours by noting productive time, unproductive time and personal time. The results from the observations of researchers through the characteristics of harvest workers that affect the characteristics of age and height characteristics, it is proven that the age of 20 - 29 years is faster to reach the target or basis compared to the age of 30 - 49 years. And the characteristics of height have an effect on reaching the target, it is proven that height 170 - 179 cm reaches the target or base faster than 150 - 159 cm. And the observations of researchers from 16 respondents harvest productive working time an average of 73.52%, 17.20% unproductive time and 9.28% personal time. Calculation of the need for harvest workers in 1 division (763.33 ha) results in 33,644 rounded up to 34 harvest workers, the results needed in 1 division (763.33 ha) through the calculation of the time of completion of tasks (WPT).